In our mothers' house - Polacco, Patricia (New York : Philomel Books, 2009)
Three young children experience the joys and challenges of being raised by two mothers.
School Library Journal.
Library Media Connection starred.
Booklist.
3.9
K-3
3.9.
Keywords: Mothers -- Juvenile fiction; Families -- Juvenile fiction; Lesbians -- Juvenile fiction; Homosexuality -- Juvenile fiction; Mothers -- Fiction; Family life -- Fiction; Lesbians -- Fiction; Homosexuality -- Fiction; Mothers -- Fiction; Family life -- Fiction; Lesbians -- Fiction; Homosexuality -- Fiction